👤

Jonny is writing a program for a video game. For one part of the game he uses the

rule given below to move objects on the screen. Showing all your work, give the output that the rule gives for the inputs.

(x, y) --> (x-8.2, y+3.6)


First input: (7.6, 9.3)


Second input: (10.5, -2.1)

Answer :

Answer:

[tex](-0.6,12.9)[/tex]

[tex](2.3,1.5)[/tex]

Step-by-step explanation:

Given:  For one part of the game, Jonny uses the  rule [tex](x,y)[/tex] → [tex](x-8.2,y+3.6)[/tex] to move objects on the screen.

To find: outputs for the given inputs

Solution:

Given rule is [tex](x,y)[/tex] → [tex](x-8.2,y+3.6)[/tex]

Put the first input as [tex](x,y)=(7.6,9.3)[/tex]

Output is [tex](x-8.2,y+3.6)=(7.6-8.2,9.3+3.6)=(-0.6,12.9)[/tex]

Given rule is [tex](x,y)[/tex] → [tex](x-8.2,y+3.6)[/tex]

Now, put input the second input as [tex](x,y)=(10.5,-2.1)[/tex]

Output is [tex](x-8.2,y+3.6)=(10.5-8.2,-2.1+3.6)=(2.3,1.5)[/tex]

Answer:

(-3.2 , 12.3)

(0.7 , 3.6)

The rule :

(x, y)→(x−7.5, y+6.8)

For the x - coordinate ; Subtract 7.5

For the y - coordinate `; add 6.8

First input : (4.3, 5.5)

Output :

x = 4.3 - 7.5 = - 3.2

y = 5.5 + 6.8 = 12.3

Output = (4.3, 5.5) →(-3.2 , 12.3)

Second input : (8.2, -3.2)

Output :

x = 8.2 - 7.5 = 0.7

y = - 3.2 + 6.8 = 3.6

Output = (8.2, -3.2)→(0.7 , 3.6)

The outputs obtained are :

(-3.2 , 12.3) and (0.7 , 3.6)